Atherogenic Index of Plasma Is an Independent Risk Factor for Coronary Artery Disease and a Higher SYNTAX Score. (February 2021) - Wang, Luzhao; Chen, Fangyao; Xiaoqi, Chai; Yujun, Chen; Zijie, Li
We aimed to identify the best diagnostic cutoff value of the atherogenic index of plasma (AIP) for coronary artery disease (CAD) and its correlation with the SYNTAX score (SS). From January 2016 to December 2019, 2253 patients with CAD and 1347 non-CAD patients with complete data were included in the study. Coronary angiography was performed using the Judkins technique, and the SS was calculated using network software. There were differences in age, body mass index, total cholesterol, triglyceride, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol levels, and AIP between groups (all P < .01). Multivariate logistic regression analysis showed that AIP was an independent risk factor for CAD and a high SS (SS ≥ 23) with adjusted odds ratios of 2.248 (95% CI: 1.666-3.032, P < .01) and 1.623 (95% CI: 1.118-2.358, P < .01) per standard deviation increase. Receiver operating characteristic curve analysis revealed that the best diagnostic cutoff value of AIP for the prediction of CAD and SS ≥ 23 was 2.035 and 2.23, the specificity was 61.8% and 65.7%, the sensitivity was 76.4% and 54.9%, the Youden index was 0.382 and 0.206, and the area under the curve was 0.733 (95% CI: 0.717-0.750, P < .01) and 0.653 (95% CI: 0.630-0.676, P < .01). Atherogenic index of plasma, as a biomarker, may assist in the prevention of CAD in the Chinese population.